Chip Floorplanning Optimization Using Deep Reinforcement Learning - Wang, Shikai; Zhang, Haodong; Zhou, Shiji; Sun, Jun; Shen, Qi (International Journal of Computer and Information System (IJCIS), 2024)
This paper presents a new method for chip floorplanning optimization using deep learning (DRL) combined with graph neural networks (GNNs). The plan addresses the challenges of traditional floor plans by applying AI to space design and intelligent space decisions. Three-head network architecture, including a policy network, cost network, and reconstruction head, is introduced to improve feature extraction and overall performance. GNNs are employed for state representation and feature extraction, enabling the capture of intricate topological information from chip netlists. A carefully designed reward function incorporating wire length minimization, area utilization, and timing constraint satisfaction guides the DRL agent toward high-quality floorplan solutions. An exploration bonus based on reconstruction error addresses the sparse reward problem. Extensive testing of the ISPD 2005 benchmarks demonstrated the effectiveness of the proposed approach, consistently operating on a state-of-the-art basis. Significant improvements include an average 31.4% reduction in half-perimeter wire length (HPWL) and a 34.2% reduction in breach time compared to the best baseline performance. The process scalability and robustness are evaluated, showing performance in various circuits and different perturbations. This research advances AI-driven electronic device design and paves the way for better chip design processes.